2021
DOI: 10.21608/ebwhj.2021.83000.1145
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Uterocervical Angle and Prediction of Spontaneous Preterm Birth

Abstract: Aim: This study aimed to determine whether a novel ultrasonographic marker, uterocervical angle, correlates with risk of spontaneous preterm birth. Materials and Methods: In the present prospective, cohort, study, we included 197 singleton pregnant women at Ain shams university maternity hospital (outpatient obstetrics clinics and emergency department. The mean age of the included women was 27.2 ± 4.8 years while the mean party was 2.2 ±1.3. The mean BMI was 33.4 ± 2.6Kg/m2. Results: In the present study, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…As shown in Table 1, the mean CL was signi cantly shorter in the participants who delivered preterm than in those who delivered at term, and the mean UCA was signi cantly greater in those who delivered preterm. These results were in agreement with the ndings of previous studies conducted in unselected singleton pregnant women; the UCA was signi cantly wider in singleton pregnant women with spontaneous PTB [21][22][23][24][25]. The combination of pressure applied the surrounding pelvic organs, more importantly from the growing uterus during pregnancy, could result in the alteration of the internal ostium (os) and cervical function [26].…”
Section: Discussionsupporting
confidence: 91%
“…As shown in Table 1, the mean CL was signi cantly shorter in the participants who delivered preterm than in those who delivered at term, and the mean UCA was signi cantly greater in those who delivered preterm. These results were in agreement with the ndings of previous studies conducted in unselected singleton pregnant women; the UCA was signi cantly wider in singleton pregnant women with spontaneous PTB [21][22][23][24][25]. The combination of pressure applied the surrounding pelvic organs, more importantly from the growing uterus during pregnancy, could result in the alteration of the internal ostium (os) and cervical function [26].…”
Section: Discussionsupporting
confidence: 91%
“…A total of 192 articles were retrieved from PubMed, Embase, the Cochrane database, WHO ICTRP, Web of Science, and ClinicalTrials.gov and through manual search. After excluding duplicates and ineligible studies, 22 studies were included in the qualitative analysis, including 11 prospective cohort studies, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 7 retrospective cohort studies, 24 , 25 , 26 , 27 , 28 , 29 , 30 and 4 case-control studies. 31 , 32 , 33 , 34 Of note, 1 study was not included in the meta-analysis because of incomplete data.…”
Section: Resultsmentioning
confidence: 99%
“…All 22 studies included in the qualitative analysis compared UCA in sPTB and term births, with 18 studies showing a statistically significant difference 13 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 27 , 29 , 30 , 31 , 32 , 33 , 34 and 4 studies showing no difference. 14 , 17 , 26 , 28 Of note, 21 studies were included in the quantitative analysis, as shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations